Tanzania - Public Expenditure Review (Vol. 2 of 2) : Consolidating the Medium Term Expenditure Framework - World Bank (Washington, DC, 2013)
This Public Expenditure Review (PER) for FY00, provided support to the Government of Tanzania in the preparation of its budget, and Medium Term Expenditure Framework (MTEF), and performed as well an external evaluation of the country's budget performance. The report contains two volumes, the Main Report (v. I) first describes the main features of the PER process, to then present the main findings emerging from a review of fiscal performance, and public expenditure management in Tanzania. A discussion of systemic fiscal issues, critical to enhancing the effectiveness of public expenditure follows, to reach a series of updated sectoral expenditure reviews, prioritizing on education, health, water, agriculture, works, land and justice. Volume II, presents the Government's MTEF for FY-01/03, in which the macroeconomic context is described, providing a cross sectoral MTEF within the priority sectors. In addition, a detailed discussion of the public sector reform program is presented, including discussions on the HIV/AIDS epidemic, identified as a key challenge to development efforts, requiring a multi-sectoral approach to contain its spread. Despite progress in consolidating the budget process, and macroeconomic policy, the transitional status of the country's economy, makes macroeconomic management particularly difficult. The report suggests rethinking the MTEF's contingency plans, within a flexible framework to further improve the linkages between prioritization, and the budgetary process.